2021
DOI: 10.3389/fnagi.2021.660621
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructural Damage Associated With Gait Abnormalities in Idiopathic Normal Pressure Hydrocephalus

Abstract: Background: Idiopathic normal pressure hydrocephalus (iNPH) is a common disease in elderly adults. Patients with iNPH are generally characterized by progressive gait impairment, cognitive deficits, and urinary urgency and/or incontinence. A number of radiographic studies have shown that iNPH patients have enlarged ventricles and altered brain morphology; however, few studies have focused on the relationships between altered brain structure and gait dysfunction due to iNPH. Thus, this study aimed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Hattori et al (2012) also obtained the same result in the conduction bundle specificity analysis of iNPH patients. Tang et al (2021) showed that iNPH patients with more WMH had poorer gait performance, and fiber bundles were most significantly correlated with gait index. In patients with iNPH, the white matter FA value in the prefrontal area is decreased.…”
Section: Discussionmentioning
confidence: 94%
“…Hattori et al (2012) also obtained the same result in the conduction bundle specificity analysis of iNPH patients. Tang et al (2021) showed that iNPH patients with more WMH had poorer gait performance, and fiber bundles were most significantly correlated with gait index. In patients with iNPH, the white matter FA value in the prefrontal area is decreased.…”
Section: Discussionmentioning
confidence: 94%
“…The exact aetiology of iNPH has yet to be fully understood [ 104 ]. It has recently been suggested that the glymphatic system may be implicated in iNPH pathogenesis [ 105 ], with studies showing a significant decrease in glymphatic clearance efficiency for subjects with iNPH relative to healthy controls [ 105 , 106 ].…”
Section: Glymphatic System and Idiopathic Normal Pressure Hydrocephalusmentioning
confidence: 99%
“…BBB dysfunction has also been linked to impaired neurovascular functioning in iNPH patients, similar to concussion patients [9]. White matter structure abnormalities are observed in both iNPH and CTE, with studies demonstrating altered tissue diffusivities post-concussions [9,10]. Finally, ventricular dilation is common to both CTE and iNPH [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…White matter structure abnormalities are observed in both iNPH and CTE, with studies demonstrating altered tissue diffusivities post-concussions [9,10]. Finally, ventricular dilation is common to both CTE and iNPH [6,10].…”
Section: Introductionmentioning
confidence: 99%